Fabrication and Evaluation of Quercetin Nanoemulsion: A Delivery System with Improved Bioavailability and Therapeutic Efficacy in Diabetes Mellitus - Manohar Mahadev; Hittanahalli S. Nandini; Ramith Ramu; Devegowda V. Gowda; Zainab M. Almarhoon; Mohammed Al-Ghorbani; Yahia N. Mabkhot (MDPI AG, 2022)
The current study was intended to fabricate and evaluate ultrasonically assisted quercetin nanoemulsion (Que-NE) for improved bioavailability and therapeutic effectiveness against diabetes mellitus in rats. Ethyl oleate, Tween 20, and Labrasol were chosen as oil, surfactant, and cosurfactant, respectively. Box-Behnken design (BBD) was employed to study the influence of process variables such as % surfactant and cosurfactant mixture (Smix) (5 to 7%), % amplitude (20-30%) and sonication time (2.5-7.5 min) on droplet size, polydispersibility index (PDI), and % entrapment efficiency (%EE) were studied. The optimization predicted that 9% Smix at 25% amplitude for 2.5 min would produce Que-NE with a droplet size of 125.51 nm, 0.215 PDI, and 87.04% EE. Moreover, the optimized Que-NE exhibited appreciable droplet size and PDI when stored at 5, 30, and 40 °C for 45 days. Also, the morphological characterization by transmission electron microscope (TEM) indicated the spherical shape of the optimized nanoemulsion. Furthermore, the Que-NE compared to pure quercetin exhibited superior release and enhanced oral bioavailability. The streptozocin-induced antidiabetic study in rats revealed that the Que-NE had remarkable protective and therapeutic properties in managing body weight, blood glucose level, lipid profile, and tissue injury markers, alongside the structure of pancreatic β-cells and hepatocytes being protected. Thus, the developed Que-NE could be of potential use as a substitute strategy for diabetes.